Preparation and dielectric properties of i1.5Zn 1.0Nb1.5O7 and Bi1.5Zn 0.92Nb1.5O6 92 pyrochlore ceramics - (:unkn) unknown (My University, 2010)
Bi1 5Zn1 0Nb1 5O7 and Bi 1 5Zn0 92 Nb1.5 O 6 92 pyrochlore compositions were prepared and investigated by X-ray diffraction (XRD) and scanning electron microscopy (SEM) and their dielectric properties were measured. XRD of Bi1.5 Zn 092 Nb 1.5 O 6.92 gave only single phase pyrochlore but second phases were observed in the XRD of Bi1.5Zn1.0Nb1.5O 7. SEM supported X-ray results but in the microstructure of Bi 1 5Zn1.0Nb1.5O7 composition a Zn-rich phase was also observed in additon to pyrochlore and ZnO. Bi 1.5Zn092Nb1.5O6 92 pyrochlore had higher dielectric constant and lower loss values than Bi1.5ZnNb 1.5O7 composition between 25-200 °C in the frequency range of 10 kHz-2 MHz, possibly due to presence of second phases in Bi 1.5ZnNb1.5O7.
Keywords: Bismuth zinc niobate pyrochlore; Ceramic dielectrics; Dielectric properties